1999
DOI: 10.1037/0012-1649.35.1.175
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in emotional expressivity and self-regulation during early infancy.

Abstract: Eighty-one 6-month-old infants and their mothers were videotaped in Tronick's face-to-face still-face paradigm to evaluate gender differences in infant and maternal emotional expressivity and regulation. Male infants had greater difficulty than female infants in maintaining affective regulation during each episode, including the still face. Mother-son dyads had higher synchrony scores than mother-daughter dyads but took longer in repairing interactive errors. In addition, maternal affect, matching, rate of cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
315
4
11

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(370 citation statements)
references
References 32 publications
40
315
4
11
Order By: Relevance
“…Instead, it is possible that they arose from differences in the ways boys and girls respond to the Still‐Face stressor. For example, different consequences of early social interaction with mothers in males and females have been described, indicating that males may be more affected in the still‐face procedure by maternal sensitivity than girls (Warren & Simmens, 2005; Weinberg, Tronick, Cohn, & Olson, 1999). As a result, maternal sensitivity may be more strongly associated with vagal reactivity in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it is possible that they arose from differences in the ways boys and girls respond to the Still‐Face stressor. For example, different consequences of early social interaction with mothers in males and females have been described, indicating that males may be more affected in the still‐face procedure by maternal sensitivity than girls (Warren & Simmens, 2005; Weinberg, Tronick, Cohn, & Olson, 1999). As a result, maternal sensitivity may be more strongly associated with vagal reactivity in males than in females.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth composite addressed periods in which the infant looked at the parent's face (sum of social attend and social play) and was termed social orientation. The monadic phases system has been used extensively in research on parent-infant affective matching in healthy and high-risk populations (Cohn & Tronick, 1988;Feldman, 2003;Feldman et al, 1999;Field et al, 1990;Lester et al, 1985;Tronick et al, 2005;Weinberg et al, 1999).…”
Section: Coding Infancymentioning
confidence: 99%
“…The fourth composite addressed periods in which the infant looked at the parent's face (sum of social attend and social play) and was termed social orientation. The monadic phases system has been used extensively in research on parent-infant affective matching in healthy and 603 BACKGROUND EMOTIONS, SYNCHRONY, AND SYMBOLIC EXPRESSION high-risk populations (Cohn & Tronick, 1988;Feldman, 2003;Feldman et al, 1999;Field et al, 1990;Lester et al, 1985;Tronick et al, 2005;Weinberg et al, 1999).Coding of the videotapes was conducted by four graduate students following extensive training. Coding was conducted in 1-s frames for 3 min of the interaction: the 2nd, 3rd, and 4th minutes, the most pronounced period of play at this age that begins after an orientation period and once the infant's gaze is focused on the parent's face.…”
mentioning
confidence: 99%
“…Most studies presented their finding that girls have better emotion regulation than boys. The difference in emotion regulation by gender is known to originate from biological difference (such as disposition), cultural difference or socialization process [35][36][37][38]. According to neuroscience researches that are being conducted actively in recent years, genderbased differences are reported in close connection to emotion regulation [39], which implies the probability of gender-based discrepancy due to biological sex differences.…”
Section: Introductionmentioning
confidence: 99%
“…However, the intervention with regard to gambling problem requires identification of specific path between variables of gambling problem. From this context, the present study is a cross-sectional study, with a goal to identify the specific path between the variables of gambling problem.Meanwhile, many studies about emotion regulation reported the difference in emotion regulation by gender [35,36]. Most studies presented their finding that girls have better emotion regulation than boys.…”
mentioning
confidence: 99%